2008
DOI: 10.1128/iai.00632-08
|View full text |Cite
|
Sign up to set email alerts
|

Pmp-Like Proteins Pls1 and Pls2 Are Secreted into the Lumen of the Chlamydia trachomatis Inclusion

Abstract: The obligate intracellular pathogen Chlamydia trachomatis secretes effector proteins across the membrane of the pathogen-containing vacuole (inclusion) to modulate host cellular functions. In an immunological screen for secreted chlamydial proteins, we identified CT049 and CT050 as potential inclusion membrane-associated proteins. These acidic, nonglobular proteins are paralogously related to the passenger domain of the polymorphic membrane protein PmpC and, like other Pmp proteins, are highly polymorphic amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
31
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 48 publications
8
31
1
Order By: Relevance
“…Immunoblot analysis of column input indicated detectible levels of CopB and CopB2 as well as controls for inclusion membrane protein (IncG) or intact bacteria (CdsD and CdsJ) in infected but not mock-infected material. As expected, CdsD and CdsJ were detected solely in the bottom column fractions and likely corresponded to sedimentation of intact chlamydiae as seen previously (18,27). Detection of IncG in fractions 2 to 7 was also as expected and was consistent with membrane association.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Immunoblot analysis of column input indicated detectible levels of CopB and CopB2 as well as controls for inclusion membrane protein (IncG) or intact bacteria (CdsD and CdsJ) in infected but not mock-infected material. As expected, CdsD and CdsJ were detected solely in the bottom column fractions and likely corresponded to sedimentation of intact chlamydiae as seen previously (18,27). Detection of IncG in fractions 2 to 7 was also as expected and was consistent with membrane association.…”
Section: Resultssupporting
confidence: 59%
“…Semiconfluent HeLa monolayers were mock treated or infected as described above with C. trachomatis L2 at a multiplicity of infection (MOI) of 10 or 1 where indicated in the figure legends. Separation of membranes through sucrose density gradients was accomplished using modifications of previously reported methods (18,27). Briefly, HeLa cells cultured in T75 flasks were mock treated or infected with C. trachomatis L2 (MOI of 1) for 24 h, and material was scraped into 8 ml of ice-cold sucrose buffer (10 mM Tris, pH 7.5, 1 mM EDTA, 0.25 M sucrose,) supplemented with protease inhibitors (complete cocktail; Roche).…”
Section: Methodsmentioning
confidence: 99%
“…Screening via microarray of the transcriptional profiles of CM972, CM3.1, and CTD153 revealed a conserved group of PRCL. This was further confirmed at the transcriptional level by quantitative PCR in these plasmid-cured strains and in plasmid-deficient clinical isolates and at the level of protein expression for Pls1 encoded by CT049 (20) and for glycogen synthase. We note that of the chromosomal loci previously described as differentially transcribed in strain 25667R in the investigation of Carlson et al (6), four loci, including CTL0071, CTL0397, CTL0638, and glgA, showed similar expression in CTD153, while CTL0305 and CTL0339 proved to be differentially transcribed when investigated as orthologs of the candidate PRCLs, CT049 and CT084.…”
mentioning
confidence: 72%
“…Immunoblotting of chlamydial strains was performed using anti-Pls1 antibody (20), provided by Raphael Valdivia, and anti-Mip antibody (4), provided by Sylvette Bas. Serovar D-specific anti-Momp monoclonal antibody used to confirm the lineage of CTD153 was a generous gift of Byron E. Batteiger.…”
mentioning
confidence: 99%
“…To ensure successful completion of the intracellular growth, Chlamydia has evolved multiple strategies for overcoming host defense mechanisms. One strategy is to secrete proteins outside of the chlamydial organisms for modifying intrainclusion lumenal environments (14), decorating inclusion membrane (15)(16)(17)(18), and/or manipulating host signaling pathways in host cell cytosol (19)(20)(21)(22)(23). Some of the secreted proteins are pre-existing proteins associated with the infectious EBs (24)(25)(26), whereas others are newly made during infection (19).…”
mentioning
confidence: 99%